A GIS-based approach for hurricane hazard and vulnerability assessment in the Cayman Islands. (May 2015) - Taramelli, A.; Valentini, E.; Sterlacchini, S.
Abstract: Coastal areas are complex systems that represent the interface between the human, physical and natural components. This paper describes the design, development and application of a conceptual foundation for a quantitative integrated coastal element vulnerability assessment using the up to date Source–Pathway–Receptor–Consequence (SPRC) approach. It is a conceptual model that combines a well-established approach in the field of waste and pollution management with the possibility of introducing the concept of system diagrams. Through the implementation of hazard classification, the approach leads to critical facilities identification and the loss estimation for specific hazards when different types of buildings are selected. In the example of Cayman Islands, the presence of exposed elements at risk, as the port or the airport, named critical facilities, drives serious potential damage effects due to high winds and storm surge. This approach provides both a spatial data infrastructure design, for collecting, storing and managing critical facilities information and a vulnerability assessment procedures for structural and operational components, concerning coastal zones affected by hurricane and related hazards. The final part of the paper synthesizes the conceptual treatment of coastal vulnerability in the Grand Cayman Island and underlines the ready-to-use GIS based vulnerability methodologies for risk assessment allowing to build capacity and resilience of the local communities. Highlights: "Provision of Services to Caribbean OCTs: GIS and Vulnerability Assessment" The R3i – programme. Implementation of vulnerability analysis hazard classification leads to critical facilities identification. Serious potential damages effects due to high winds and storm surge for hurricane related hazards in Cayman Island.